(untitled) (PERcursos Linguísticos, 2022)
Abstract: This article presents reflections on the work of a teacher in the context of a pandemic, which demands new ways of acting and thinking, in order to create and (re)create professional actions. We seek to propose a dialogue with three teachers so that they would have the opportunity to talk about their teaching work-related feelings and meanings. This investigation is included in the theoretical-methodological field of Sociodiscursive Interactionism, in dialogue with the principles of the Clinic of Activity. The results point out that we must be aware of the situations, elements, and meanings around the teaching acting, as this acting is surrounded by multiple social coercions.